On-wafer RF stress and trapping kinetics of Fe-doped AlGaN/GaN HEMTs. (September 2018) - Rzin, M.; Chini, A.; De Santi, C.; Meneghini, M.; Hugger, A.; Hollmer, M.; Stieglauer, H.; Madel, M.; Splettstößer, J.; Sommer, D.; Grünenpütt, J.; Beilenhoff, K.; et al.
Abstract: In this paper, we investigate the trapping effects, of iron doped AlGaN/GaN HEMTs, before and after on-wafer 24 hour RF stress test. First, we study the trap centers responsible of the current collapse at different on-state bias and temperature conditions. Second, we investigate 24 hour RF stress effect on the trapping kinetics. By filling traps under off-state condition with high drain-source voltage, we have identified two prominent traps labelled E1 and E2 with activation energies of 0.7 eV and 0.6 eV under the conduction band, respectively. An increase of the amplitude of the trap centers E1 and E2 by 22.9% and 15.8% respectively is noticed during the RF stress. This result suggests that the degradation observed during RF stress might have induced a density increase of the traps involved in the E1 and E2 trap signatures responsible on the current collapse.